Sílica coloidal como agente ligante e fonte mulitizadora em concretos refratários - Magliano, Marcus Vinicius Morais (Universidade Federal de São Carlos, 2009)
The recent development of refractory castables for high temperatures applications are closely related to binders technology, especially those presenting superior performance and installation properties. The calcium aluminate cement (CAC), one of the most used binder for refractories, has passed over the last years through several enhancements leading to an increase of monolithic use instead of traditional bricks. The continuous search for new binder s came to the development of several binding systems such as hidratable alumina, and others. Nowadays, with the strong presence of nanotechnology on all science fields, new binders containing nano structures are being studied. The colloidal silica is one of the most studied nano structured binder. It has three mains advantages, that places it as a promising substitute for CAC in some applications. First it contains nano pores that facilitates the drying process. Second, it does not have hydraulics components, avoiding reduction on mechanical strength at intermediate temperatures. Third, it is free of CaO and others elements that could deteriorate the performance at high temperatures. Furthermore, the colloidal silica is a highly reactive source of SiO2. This work aims to study the influence of hidratable alumina, CAC and colloidal silica for mullitization on alumina based compositions. The objective is to compare green and final properties as well as the amount and morphology of the mullite formed. The results indicated better drying conditions, superior high temperatures properties and suggested higher mullitization for castables using colloidal silica. However, the molding and curing steps should be well controlled to avoid cracks due to high reactiveness of this binder.
Colloidal silica as binder and source of mulitization for refractories castables
Keywords: Materiais refratários; Ligantes; Concretos refratários; Sílica coloidal; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA